2021
DOI: 10.26508/lsa.202101084
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative proteomics identifies PTP1B as modulator of B cell antigen receptor signaling

Abstract: B cell antigen receptor (BCR) signaling is initiated by protein kinases and limited by counteracting phosphatases that currently are less well studied in their regulation of BCR signaling. Here, we used the B cell line Ramos to identify and quantify human B cell signaling components. Specifically, a protein tyrosine phosphatase profiling revealed a high expression of the protein tyrosine phosphatase 1B (PTP1B) in Ramos and human naïve B cells. The loss of PTP1B leads to increased B cell activation. Through sub… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 83 publications
0
6
0
Order By: Relevance
“…PTP1B occupies a central position in oncogenic signaling. In the last decade, several substrates of this phosphatase have been validated [2224]. However, additional substrates that mediate the oncogenic effects of PTP1B in different types of cancer remain to be determined.…”
Section: Resultsmentioning
confidence: 99%
“…PTP1B occupies a central position in oncogenic signaling. In the last decade, several substrates of this phosphatase have been validated [2224]. However, additional substrates that mediate the oncogenic effects of PTP1B in different types of cancer remain to be determined.…”
Section: Resultsmentioning
confidence: 99%
“…We repeated this experiment for another SH3 domain-containing protein, ARHGAP12, that has been identified in proteomics studies as a PTP1B interactor, but for which the binding site on PTP1B has not been determined. 14 Coimmunoprecipitation of this interactor was also dependent on the proline-rich region (Figure 5C). These results show that the proline-rich region is important for both Grb2 and ARHGAP12 binding to PTP1B in cells.…”
Section: Grb2 Binding Alters Ptp1b Activity Against Phosphopeptide Su...mentioning
confidence: 90%
“…Several recent proteomics studies have revealed a suite of protein interactors for the tyrosine phosphatase PTP1B. 14,15,39 The functional consequences of many of these non-substrate PTP1B interactions remain unknown. Indeed, very few proteins have been shown to directly regulate PTP1B activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The germinal center-derived Burkitt lymphoma B cell line Ramos is a useful system for learning more about human B cell biology (23,35,36). These B cells have been frequently used for signal transduction studies (37) and their transcriptome, proteome, and surfacesome have been determined (38)(39)(40). Furthermore, with the CRISPR/Cas-9 technology, it is now straightforward to introduce mutations or gene KOs in this cell line.…”
Section: Discussionmentioning
confidence: 99%